Human Rights and Transhumanism: From Natural Rights to Trans-Natural Rights - Grégor Puppinck (Chrześcijaństwo-Świat-Polityka)
This text explores the evolution of human rights throughout the 20th century. The text analyses the transition from traditional conceptions of human dignity rooted in human nature to emerging notions influenced by transhumanist ideologies. The analysis delves into contrasting perspectives on human dignity, comparing the Aristotelian-Christian tradition, which values the unity of body and soul, with materialist philosophies that prioritize intellect over physicality. The document outlines how these philosophical shifts have led to the emergence of “disembodied dignity” and the promotion of “anti-natural” and eventually “trans-natural” rights, which prioritize individual will over inherent human nature. Through historical analysis and philosophical inquiry, this text examines how these evolving ideologies have influenced legal interpretations, societal values, and the trajectory of human rights discourse.